Application of Restorative Justice in Criminal Offences of Domestic Violence Domestic Violence in Indonesia - Maharani Tarigan Sibero, Sari; Adianto Mau, Hedwig; Achmad Darodjat, Tubagus (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2026)
This research examines the application of Restorative Justice in the settlement of criminal acts of Domestic Violence (DV) in Indonesia using a normative legal approach. The focus of the research lies on analyzing laws and regulations related to the application of restorative justice in handling domestic violence cases. Restorative Justice is proposed as a more humane alternative to the dominant retributive justice system, with the aim of improving relationships between victims and perpetrators and providing space for healing. This research concludes that although the application of Restorative Justice faces significant challenges, such as social norms that discourage victims from reporting and the unpreparedness of law enforcement officials in applying the principles, this approach has the potential to offer a more effective solution in reducing domestic violence. Through an analysis of existing legal policies, this research provides recommendations to strengthen the implementation of Restorative Justice in Indonesia by involving more parties, including law enforcement officials, social institutions, and communities.